The Best Model of the Autoregressive Integrated Moving Average (ARIMA) Method for Predicting the Exchange Rate of the Indonesian Rupiah Against the US Dollar (USD) for the Period July 2025 - June 2026 - Putri, Desiana; Bohori, Meliyana (Jurnal Matematika, Statistika dan Komputasi, 2026)
The exchange rate fluctuations are an important indicator that affects the stability of a country's economy, including Indonesia. This condition makes accurate exchange rate forecasting a strategic necessity in supporting economic decision-making and fiscal policy. One of the methods widely used for exchange rate forecasting is Autoregressive Integrated Moving Average (ARIMA), which has proven effective in capturing patterns and trends in historical data. Therefore, this study was conducted to find the best model for forecasting the exchange rate of the Rupiah against the US Dollar (USD) using the Autoregressive Integrated Moving Average (ARIMA) method. The data used is monthly data on the exchange rate of the Rupiah against the USD for the period January 2015 to June 2025. By identifying, estimating, and diagnosing the model, the best ARIMA model was obtained that met the white noise assumption and produced the lowest AIC/BIC value.